2005
DOI: 10.1161/01.cir.0000155617.54749.09
|View full text |Cite
|
Sign up to set email alerts
|

QTc Prolongation by Grapefruit Juice and Its Potential Pharmacological Basis

Abstract: We found a significant QTc prolongation by grapefruit juice in healthy volunteers, probably caused by block of HERG channels by flavonoids. These findings reveal new perspectives on the potential for dietary modification of cardiac electrophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 19 publications
5
61
0
1
Order By: Relevance
“…However, inhibition of the same current has also been linked to antiarrhythmic properties and several well-known antiarrhythmics, like amiodarone, dronedarone, and ajmaline inhibit I Kr [78][79][80]. Only recently, we screened a broad spectrum of flavonoids and showed that among others, the citrus flavonoids hesperetin and naringenin potently block hERG potassium channels, which form the molecular basis of I Kr in humans [81][82][83]. Similar results could be found for EGCG, the active component of green tea [84].…”
Section: Inhibition Of Cardiac Potassium Currentssupporting
confidence: 71%
“…However, inhibition of the same current has also been linked to antiarrhythmic properties and several well-known antiarrhythmics, like amiodarone, dronedarone, and ajmaline inhibit I Kr [78][79][80]. Only recently, we screened a broad spectrum of flavonoids and showed that among others, the citrus flavonoids hesperetin and naringenin potently block hERG potassium channels, which form the molecular basis of I Kr in humans [81][82][83]. Similar results could be found for EGCG, the active component of green tea [84].…”
Section: Inhibition Of Cardiac Potassium Currentssupporting
confidence: 71%
“…Using this model, the IC 50 of naringenin on HERG inhibition was 173 µ M , which is similar to other reports [8, 9]. Since the follicular membrane surrounding the oocyte may impede the access of the drug to the HERG channel, inhibitory effects of blocking agents may be affected.…”
Section: Discussionsupporting
confidence: 86%
“…Recently, significant QTc prolongation by grapefruit juice in healthy volunteers has been reported. This has been attributed to human ether-a-go-go-related gene (HERG) blockade by grapefruit flavonoids [8]. Naringenin, the principal flavonoid in grapefruit juice, has been identified as the most potent HERG channel blocker among several dietary flavonoids [9].…”
Section: Introductionmentioning
confidence: 99%
“…During the intervention, blood was sampled every 3 mo to determine liver markers, including alanine aminotransferase, aspartate aminotransferase, g-glutamyl transferase, and alkaline phosphatase. A control electrocardiogram was performed 10 d after the beginning of each intervention period and at each visit to avoid any risk of a prolonged corrected Q-T interval in response to grapefruit consumption (18).…”
Section: Methodsmentioning
confidence: 99%